Post-colectomy enteritis—a rare complication in a patient with ulcerative colitis - Julia Wanzl; Sandra Nagl; Alanna Ebigbo; Lena Anthuber; Florian Sommer; Michael Hoffmann; David Rafael Marques Pinto; Dmytro Vlasenko; Irene Kleinlein; Elisabeth Schnoy (Therapeutic Advances in Gastroenterology)
Colectomy is the surgical treatment of choice in patients with severe or complicated ulcerative colitis. Post-colectomy enteritis (PCE) is a rare condition that can develop after proctocolectomy and has been described only in a few individual cases so far. We report the case of a 46-year-old patient with severe and treatment-refractory ulcerative colitis who underwent colectomy. A few days after surgery, the patient presented with acute anemia and hematemesis. Esophagogastroduodenoscopy showed massive inflammation of the duodenum and jejunum. The life-threateningly ill patient was admitted to the intensive-care unit and treated for severe PCE with ciclosporin and corticosteroids. PCE is a distinct inflammation of the small intestine shortly after colectomy. The patient recovered fully and was discharged after prolonged recovery and long-term intensive care therapy.